Pelaksanaan Kegiatan Promosi Kesehatan Rumah Sakit (PKRS) di Rumah Sakit Bhayangkara Tingkat II Semarang - Agnes Nova Astrida Purba; Syamsulhuda BM; Zahroh Shaluhiyah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The Minister of Health has made vision and missions for increasing health development. Hospital is a health facility that included in the subsystem of health effort so it must be integrated into the health system, therefore the Minister of Health held a development of Health Promotion in Hospital. The basic strategy of Health Promotion in Hospital is empowering that supported by partnerships, advocacy and building atmosphere. Bhayangkara Hospital in Semarang is a government-owned hospitals that socialized about Health Promotion in Hospital, has a organization of Health Promotion in Hospital, it also acredited, which is one of the assesment is assesment of Health Promotion in Hospital, but there is no implementation of the empowerment efforts aimed at increasing knowledge of the patient, family, hospital personnel and the community around the hospital so there are still patients with recurrent disease. This research uses qualitative descriptive method with the subject of the research taken by using purposive sampling. As for the researched is input, procss and output of impelementation of health promotion in Hospital. The main informant consists of three employee of health promotion in Hospital section. As for the informant triangulation is a president director in Hospital, two patients, and two family of patients. As for the results of this research are the organization of Health Promotion in Hospital does not implemented in accordance with the functions in the standard of Health Promotion in Hospital which have been prepared by the Minister of Health because of the limited human resources so that there is no difference between the duties and functions of health promotion in Hospital and public relations and marketing.